Polygamy in the Perspective of Islamic Law and Indonesian Positive Law - Rusliadi, Ridwan (KnE Social Sciences, 2023)
The purpose of this article is to explore and analyze the legal basis for polygamy in both Islamic law and positive law in Indonesia. Polygamy refers to a man having multiple wives at the same time. In Islamic law, polygamy is permissible under certain conditions as stated in the Qur’an, specifically if the husband can treat all wives fairly. The research aims to examine the perspective of polygamy in both Islamic law and Indonesian positive law. The method used in this research is a normative juridical approach with a descriptive research approach. Data obtained will be systematically organized for further qualitative analysis. The research findings indicate that the regulation of polygamy in positive law makes it challenging for husbands to practice polygamy, whereas Islamic law does not impose excessive obstacles. The conditions for the permissibility of polygamy according to Law Number 1 of 1974 are outlined in Article 4 paragraph (2) and Article 5 paragraph (1). The legal basis for granting polygamy permits is formally stipulated in Law Number 1 of 1974 concerning marriage, Article 3 paragraph (2) alongside Article 43 PP. 9 of 1975, and Presidential Instruction Number 1 of 1991 on KHI Article 56 paragraph (3). It is essential for these two laws to be in harmony with each other to avoid conflicts and problems, especially in the context of marriage, particularly concerning polygamy. Keywords: polygamy, Islamic law, positive law